Supramolecular aggregates of cyclodextrins with co-solvent modulate drug dispersion and release behavior of poorly soluble corticosteroid from chitosan membranes. (15th November 2020) - do Nascimento, Ednaldo Gomes; de Azevedo, Eduardo Pereira; Alves-Silva, Mariana Farias; Aragão, Cícero Flávio S.; Fernandes-Pedrosa, Matheus F.; da Silva-Junior, Arnóbio Antônio
Graphical abstract: Highlights: Homogeneous dispersion of triamcinolone acetonide into chitosan membranes is not possible. Supramolecular aggregates with cyclodextrins and co-solvent improve drug-loading in membranes. The type of cyclodextrin and co-solvent concentration affect the membrane performance. A novel drug delivery device for topical application triamcinolone. Abstract: In this study, the ability of different beta-cyclodextrins to facilitate homogeneous dispersion of triamcinolone acetonide (TA) into chitosan membranes is assessed. Drug loading was assessed through atomic force microscopy (AFM), scanning electron microscopy (MEV-FEG), and X-ray diffraction analyses. Drug interactions with the co-polymer were investigated with Fourier transform infrared spectroscopy, thermal analyses. Swelling assay, and in vitro drug release experiment were used to assess TA release behavior. Undispersed particles of drug were observed to remain in the simple chitosan membranes. Hydroxypropyl-β-cyclodextrin enabled the dispersion of TA into chitosan membranes and subsequent sustained drug release. In addition, the membrane performance as a drug delivery device is improved by adding specified amounts of the co-solvent triethanolamine. The experimental data presented in this study confirm the utility of our novel and alternative approach for obtaining a promising device for slow and controlled release of glucocorticoids, such as triamcinolone acetonide, for topical ulcerations.